Practitioners` multi-disciplinary perspectives of soccer talent according to phase of development and playing position - Towlson, C.; Cope, E.; Perry, J. L.; Court, D.; Levett, N. (International Journal of Sports Science & Coaching, 2019)
The study aimed to establish the perceived importance that academy soccer practitioners placed on technical/tactical, physical, psycho-social player attributes during player selection and explore whether perceptions change according to Elite Player Performance Plan phase. Seventy academy practitioners working within Elite Player Performance Plan programs (Category 1: n = 29; Category 2: n = 13 and Category 3: n = 28) completed an online survey. Psychological factors were rated significantly (p = 0.01) higher than sociological, technical/tactical, and physical factors, with recruitment staff specifically valuing psychological factors significantly (p = 0.01) more than medical staff. Youth Development phase practitioners valued sociological factors significantly (p < 0.05) more than in the Foundation phase, which was also true for physical factors. Practitioners indicated significant positional differences for most physical and technical/tactical attributes. There was no playing position effect for relative age effect or maturity. Between playing position variance of outfield players for most technical and physical attributes increased according to advancing Elite Player Performance Plan phase. Attitudes to holistic talent identification criteria likely change according to practitioner role. Therefore, this study provides evidence to suggest that Elite Player Performance Plan practitioners place less perceived importance on enhanced maturity status and relative age of players but does indicate an enhancing and significant positional preference for physical and technical/tactical attributes. Suggesting that practitioners are less likely to (de)select players based on transient, maturity-related attributes and instead place greater emphasis on specialist physical/technical position-specific attributes as players navigate the Elite Player Performance Plan pathway towards professional status.